The Stability Analyses of Tunnel Faces in Saturated Soils with Soil Arching Effect - Liu An; Xi Mingxing; Liu Jun (Geofluids)
The undesirable effect on the stability for cross-river tunnel faces considering pore water pressure was observed with the consideration of the soil arch effect by using the discrete technology for the first time. In light of the upper bound of plastic theory, an improved failure mechanism of the deep-buried tunnel face was established. A new discrete technology approach taking account into the soil arching effect was proposed to estimate the stability for cross-river tunnel faces subjected to pore water pressure. The presented approach is validated by comparing with the existing solutions as well as showing great improvements. After verification, based on the failure mechanism, this paper discusses the impact of the changing water level and the soil parameters on the normalized supporting pressure and meanwhile analyzes the variation of the shape of collapsing domain of soils ahead of the tunnel face considering the soil arching effect. The results illustrate that soils with the bigger friction angle form the arch more easily during excavation, and with higher water height, the soil arching effect appears not as obvious as expected, particularly on those soils with the smaller friction angle.